The pleasure girls - O'Hara, Gerry 1924-2023; McShane, Ian 1942-; Annis, Francesca 1944-; Kinski, Klaus 1926-1991 (British film institute, 2010)
"When Sally (Francesca Annis) moves to London to pursue a modelling career, she moves in with Angela (Anneke Wills) and Dee (Suzanna Leigh) and discovers the world of the carefree bachelor girl, over a weekend of parties and romantic encounters. With lively performances from its young ensemble cast (including Ian McShane and Klaus Kinski), this delightful drama bears all the hallmarks of director Gerry O'Hara's assured style."
Original: UK 1965
Bildformat: 1.66:1
Special features: Presented in both High Definition and Standard Definiton ; Alernative export cut (blu-ray only, 86 min) ; Alternative export sequences (DVD only, 13 min) ; Original theatrical trailer ; The rocking horse (James Scott, 1962, 25 min): atmospheric short about a romantic encounter between a teddy boy and an artist ; The meeting (Mamoun Hassan, 1964, 10 min): a young woman's unconventional encounter with a mysterious lover ; Fully illustrated booklet with contributions by Gerry O'Hara, Professor Sue Harper, and Mamoun Hassan
Verlagsnummer BFIB1086
Keywords: Single people / England / London / Drama; Man-woman relationships / Drama; London (England) / Social life and customs / Drama; Man-woman relationships; Manners and customs; Single people; England / London; Motion pictures / Great Britain; Film; DVD-Video; Blu-Ray-Disc